A problem of robust control of a system with time delay - Blizorukova, Marina; Kappel, Franz; Maksimov, Vyacheslav I. (Zielona Góra: Uniwersytet Zielonogórski)
A problem of guaranteed control is under discussion. This problem consists in the attainment of a given target set by a phase trajectory of a system described by an equation with time delay. An uncontrolled disturbance (along with a control) is assumed to act upon the system. An algorithm for solving the problem in the case when information on a phase trajectory is incomplete (measurements of a 'part' of coordinates) is designed. The algorithm is stable with respect to informational noises and computational errors.
Keywords: robust control; system with time delay